Penilaian Kondisi Bangunan Gedung Sekolah Dasar Negeri Studi Kasus di Sekolah Dasar Negeri Se-Kabupaten Madiun - Parmo Parmo; Mohammad Hadi Sucipto; Sumarkan Sumarkan (Universitas Islam Negeri Sunan Ampel Surabaya, 2016)
Facilities and infrastructure are important elements to achieve the successful education and teaching process. The procurement of adequate and standardized buildings become an effort to comply with the minimum standards of infrastructure required by the government. This study focus on conducting an analyzis the damage level at State Primary School (SDN) buildings in Madiun regency.Building condition assessment conducted through a direct surveys and then proceed by weighting the data to obtain the level of damage categorized as good, minor, moderate and heavily damaged . Among the 431 of state primary school buildings surveyed, 36.53% of the classrooms in a minor damage while 25.42% others considered heavily damaged. For the teacher's office, 38.04% were in a minor damage, while 23.23% others considered heavily damaged. For the library buildings, 38.14% of them considered in a minor damage and 24.53% others heavily damaged. For teacher latrines condition, 49.53% of teacher latrines considered heavily damaged, while 24.03% were moderate damage. While 49.82% of student latrines were heavily damaged and 23.49% others considered in a moderate damage.From the assessment, it can be concluded that the latrines facility repairment, both for teachers and students, should become top priority for the local government in the implementation of school quality improvement programs.buildings condition, level of damage, primary school building